2022
DOI: 10.3390/math10244753
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Inertial Sensor-Based Hand-Guiding Gestures Recognition Method Robust to Significant Changes in the Body-Alignment of Subject

Abstract: The accuracy of the wearable inertia-measurement-unit (IMU)-sensor-based gesture recognition may be significantly affected by undesired changes in the body-fixed frame and the sensor-fixed frame according to the change in the subject and the sensor attachment. In this study, we proposed a novel wearable IMU-sensor-based hand-guiding gesture recognition method robust to significant changes in the subject’s body alignment based on the floating body-fixed frame method and the bi-directional long short-term memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…As shown in Figure 3 (left), even if the subject performs the same action while changing pose, the same pattern of data is not always collected, and the features that affect phase recognition change, resulting in low overall recognition accuracy. Therefore, this study solves the aforementioned problem by creating the float body-fixed frame ( ), as proposed in previous our research [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 3 (left), even if the subject performs the same action while changing pose, the same pattern of data is not always collected, and the features that affect phase recognition change, resulting in low overall recognition accuracy. Therefore, this study solves the aforementioned problem by creating the float body-fixed frame ( ), as proposed in previous our research [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…This alignment ensures that the IMU sensor data remain consistent, even when the user changes posture or moves, as illustrated on the right of Figure 3 . The formation and detailed information regarding the are available in our previous research [ 20 ]. Algorithm 1.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiaoliang Zhang et al [ 11 ] who detected gestures by combining a wearable armband and a smart glove made from a customizable array of pressure sensors, achieved the recognition of 10 gestures. Haneul Jeon et al [ 12 ] proposed a novel gesture recognition method based on wearable IMU sensors and experimentally demonstrated that the method is appropriate for gesture recognition under significant changes in the subject’s body alignment during gestures. In addition, to improve the accuracy of wearable sensor-based gesture recognition algorithms, Haneul Jeon et al [ 13 ] proposed a DCGAN structure with a mode switcher for data enhancement of time-series sensor data.…”
Section: Related Workmentioning
confidence: 99%